The Use of Artificial Intelligence in Responding to Patient Questions About Anterolateral Thigh Flap Surgery for Diabetic Foot Ulcers - Llaurado, Luke J; Shah, Kishan S.; Snee, Isabel A.; Rohrich, Rachel N; Bender, Ryan J.; Episalla, Nicole C.; Youn, Richard C.; Evans, Karen K (Journal of Reconstructive Microsurgery)
Background: Diabetic foot ulcer (DFU) care represents a significant challenge in plastic and reconstructive surgery. Oftentimes, patients encounter complex articles and websites to answer questions about their surgeries, including Anterolateral Thigh (ALT) flaps. Artificial intelligence (AI) represents a new and simplified resource for DFU patients seeking information regarding their care. To assess ChatGPT’s utility as a patient resource, we evaluated the accuracy, comprehensiveness, and safety of AI-generated responses to frequently asked questions (FAQs) related to ALT flap surgery for DFU. Methods: Ten DFU and ALT flap care FAQs were posed to ChatGPT Model 3.5 in June 2024. Four plastic surgeons evaluated responses using a 10-point Likert scale for accuracy, comprehensiveness, and danger of ChatGPT's answers. Surgeons also provided qualitative feedback. Response readability was assessed using 10 readability indexes, averaged to produce a reading grade level for each response. Results: Overall, ChatGPT answered patient questions with a mean accuracy of 9.1 ± 1.2, comprehensiveness of 8.2 ± 1.5, and danger of 2.0 ± 1.0. ChatGPT answered at a mean grade level of 19.8 ± 20.1. Qualitatively, physician reviewers complimented the organizational clarity of the responses (n=4/10) and the AI’s ability to provide information on possible surgical complications (n= 4/10). While 1 response was noted to present explicitly incorrect information about pre-operative preparation protocols and when they should be initiated, the majority of responses (n=6/10) left out key post-operative information, notably dangle protocols and compression. Conclusion: ChatGPT provides accurate and comprehensive responses to FAQs related to patients undergoing ALT flap surgery for the treatment of DFUs. The AI-generated responses were praised for organizational clarity and informative content regarding surgical complications, but lacked essential post-operative care details. Therefore, while ChatGPT is a valuable informational tool, further refinement is necessary to ensure fully comprehensive information is provided to DFU patients.